Exploring light transport properties in complex photonic networks - Tang, Shiqi (Nanyang Technological University, 2024)
This dissertation explores the properties of complex photonic networks with an emphasis on light transport. Motivated by the potential of these networks to revolutionize optical systems, the study employs advanced numerical simulations to delve into their intricate behaviors and properties. We investigate transmission and reflection eigenvalues in a Buffon network as internal connectivity vary. Using detailed numerical models, we examine light scattering and propagation within these networks and how varying internal connectivity in Buffon networks affects the transmission and reflection eigenvalues, providing crucial insights into the scattering phenomena.This project examines not only the fundamental eigen- value distributions but also the critical role of network topology in determining optical responses, providing a comprehensive understanding of light-matter inter- actions in disordered systems. These contributions pave the way for designing advanced optical devices and systems, with broad implications for telecommuni- cations, materials science, and information technology.